Domestic Violence Based on Law No. 23 of 2004 Concerning the Elimination of Domestic Violence - Chrisbiantoro Chrisbiantoro; Hudi Yusuf (Journal of Social Research, 2023)
Domestic Violence is a classic problem in the world of law and gender. Even though the legal umbrella to protect victims from domestic violence already exists, namely Law Number 23 of 2004 concerning the Elimination of Domestic Violence, this has not been enough to anticipate this violence, in this case, the need for legal attention and protection from both the government, law enforcement officials, as well as from the community so that it is hoped that everyone who hears, sees, or knows about the occurrence of domestic violence is obliged to take preventive measures and provide assistance. Actually, what are the causes and what kind of protection is there for women victims of crimes of domestic violence regulated in Indonesian positive law? From this background, several problems can be raised, namely: against women victims of domestic violence and efforts to overcome them. Discussion of these issues requires research methods, while the research methods used include: approach methods, research specifications, types and sources of data, data collection methods, and data analysis methods. Based on the research above, the following results and conclusions can be obtained: legal protection for women victims of criminal acts of domestic violence has been regulated in Law No. 23 of 2004 concerning the Elimination of Domestic Violence